DISCO-2 – an ambitious earth observing student CubeSat for arctic climate research - Dideriksen, Andreas Kjær; Andersen, Mads Fredslund; Priest, Julian; Eriksen, Nikolaj Forskov; Frandsen, Mads Toudal; Melvad, Claus; Rasmussen, Tobias Frejo; Nielsen, Noah Harry Kjeldgård; Strømsnes, Cecillie Thorup; Ahlebæk, Mads Juul; Samsing, Sigrid; Larsen, Thomas Buris; et al. (Frontiers in Remote Sensing, 2024)
The severe impact of global warming, especially in the arctic region, have a multitude of consequences spanning from sea-level rises and freshening of the ocean, to significant changes to the animal life, biodiversity and species distribution. As the arctic regions are inherently remote and can be both hazardous and difficult to reach, research to improve our understanding of the climate change impact is often limited to short term field-campaigns. Here we present the Danish DISCO-2 student CubeSat mission, designed to meet the growing need for an Earth-observing platform. This mission leverages the rapid advancements in CubeSat technology over the past decades to overcome the limitations of traditional fieldwork campaigns. DISCO-2 will assist on-going arctic climate research with a payload of optical and thermal cameras in combination with novel in-orbit data analysis capabilities. It will further be capable of performing photogrammetric observations to determine ice volumes from deteriorating glaciers and provide surface temperatures, enabling studies of heat transfer between glaciers and arctic fjords. As a student satellite, the payload capabilities will also be offered to novel student research ideas throughout the mission life time. The modularity and wide range of of-the-shelf-components for CubeSats has facilitated an immense opportunity to tailor this earth observing CubeSat to accommodate specific scientific goals and further provided students at the participating universities with an unparalleled possibility to go from an initial research idea to a running CubeSat mission.